(untitled) (Baghdad Science Journal, 2021)
Emissions of particulate matter from nanopapers as well as inks and organic solvents during the printing operationand copying machines constitute a threat to human health, especially with long time exposure in closed working environments. The present study was conducted in some printing houses and copying centers of Baghdad city during February and April .The studyproved the occurrence of an air pollution problem concerning lead and zinc contents in all the study sites. The levels of Pb, Zn and Cu were collected by low volume sampler from the air of the study sites then filter papers digested and determined the heavy metals by flame atomic spectrophotometer. Particulate matter was measured by Aerocet, Microtector meter device was used to measure nitrogen dioxide, sulphur dioxide, carbon monoxide and volatile organic compounds . The highest concentrations of lead and zinc were recorded in the printing houses air (2.75μg/m3) and (51.95μg/m3) respectively. In contrast,copper concentration in the copying offices air recorded a significantly higher value (0.65μg/m3) (P>0.05) as compared to that in printing houses. Fine particulate matter(PM2.5)(particles diameter < 2.5 μm) hasrecorded the highest concentration (44.50μg/m3) in printing houses, followed by the highest concentrations of inhalable coarse particulate matter (PM10) (particles with diameter of 2.5 to 10 μm) and total suspended particulates (TSP)(the total of solid particles) (477.66 and 667.00μg/m3) respectively in printing houses. The results obviously showed the highest concentrations of carbon monoxide (CO) (6.13 ppm) and volatile organic compounds (VOCs) (21.88 ppm) in printing houses, while nitrogen dioxide (NO2) recorded its highest concentration (1.44 ppm) in copy centers. Lead, zinc, copper, PM2.5, PM10 and TSP concentrations exceeded the permissble levels in all study sites converselywith the levels of carbon monoxide , nitrogen dioxide, sulphur dioxide(SO2) and volatile organic compounds that were within permissible air quality standards.